2015
DOI: 10.1161/jaha.115.001889
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Development of Left Anterior Heart Field by Ectopic Retinoic Acid Causes Transposition of the Great Arteries

Abstract: BackgroundTransposition of the great arteries is one of the most commonly diagnosed conotruncal heart defects at birth, but its etiology is largely unknown. The anterior heart field (AHF) that resides in the anterior pharyngeal arches contributes to conotruncal development, during which heart progenitors that originated from the left and right AHF migrate to form distinct conotruncal regions. The aim of this study is to identify abnormal AHF development that causes the morphology of transposition of the great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…RA signaling influences the posterior segment of the heart tube (blue) to establish the primitive atrium and sinus venosus. For example, abnormal development of the cranial anterior SHF by local administration of RA to the second pharyngeal arches in stage 12 chick embryos (corresponding to E8.5 in mouse, Carnegie stage 10 in human) causes TGA (Narematsu, Kamimura, Yamagishi, Fukui, & Nakajima, 2015); and ablation of the caudal anterior SHF in the posterior pharyngeal arches at stage 14 (E9.0 in mouse, Carnegie stage 11 in human) causes TOF . (a) The SHF is subdivided into posterior and anterior SHFs.…”
Section: Introductionmentioning
confidence: 99%
“…RA signaling influences the posterior segment of the heart tube (blue) to establish the primitive atrium and sinus venosus. For example, abnormal development of the cranial anterior SHF by local administration of RA to the second pharyngeal arches in stage 12 chick embryos (corresponding to E8.5 in mouse, Carnegie stage 10 in human) causes TGA (Narematsu, Kamimura, Yamagishi, Fukui, & Nakajima, 2015); and ablation of the caudal anterior SHF in the posterior pharyngeal arches at stage 14 (E9.0 in mouse, Carnegie stage 11 in human) causes TOF . (a) The SHF is subdivided into posterior and anterior SHFs.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoic acid (RA), an active metabolite of vitamin A that acts through nuclear retinoid receptors, influences gene expression, alters the synthesis of proteins in the heart, and regulates embryonic development, tissue homeostasis, and cellular differentiation and proliferation [1-3]. …”
Section: Introductionmentioning
confidence: 99%
“…), suggesting potential regions responsible for specific conotruncal heart defects (Nakajima ). Indeed, laser ablation of the right SHF caused tetralogy of Fallot (TOF) (Ward et al ), and an impaired development of the left AHF by locally administrated retinoic acid, having a teratogenic effect to OFT development in human and laboratory animals, caused TGA morphology in chick embryonic heart (Narematsu et al ).…”
Section: Introductionmentioning
confidence: 99%
“…This consideration is consistent with the results from a time‐controlled deletion of Tbx1 (Xu et al ). In avian embryos, retinoic acid‐induced perturbation of AHF and laser ablation of SHF caused TGA and TOF, respectively (Ward et al ; Narematsu et al ). Taken together, it may be suggested that Tbx1 mainly functions in the SHF, which is located in the posterior (caudal) pharyngeal arches after the completion of the right ventricle and proximal OFT from the AHF.…”
Section: Introductionmentioning
confidence: 99%